Alpha lipoic acid mitigates adverse impacts of drought stress on growth and yield of mungbean: photosynthetic pigments, and antioxidative defense mechanism - Mian, Naima Hafeez; Azeem, Muhammad; Ali, Qasim; Mahmood, Saqib; Akram, Muhammad Sohail (PeerJ, 2024)
Context Exogenous use of potential organic compounds through different modes is a promising strategy for the induction of water stress tolerance in crop plants for better yield. Aims The present study aimed to explore the potential role of alpha-lipoic acid (ALA) in inducing water stress tolerance in mungbean lines when applied exogenously through various modes. Methods The experiment was conducted in a field with a split-plot arrangement, having three replicates for each treatment. Two irrigation regimes, including normal and reduced irrigation, were applied. The plants allocated to reduced irrigation were watered only at the reproductive stage. Three levels of ALA (0, 0.1, 0.15 mM) were applied through different modes (seed priming, foliar or priming+foliar). Key results ALA treatment through different modes manifested higher growth under reduced irrigation (water stress) and normal irrigation. Compared to the other two modes, the application of ALA as seed priming was found more effective in ameliorating the adverse impacts of water stress on growth and yield associated with their better content of leaf photosynthetic pigments, maintenance of plant water relations, levels of non-enzymatic antioxidants, improved activities of enzymatic antioxidants, and decreased lipid peroxidation and H2O2 levels. The maximum increase in shoot fresh weight (29% and 28%), shoot dry weight (27% and 24%), 100-grain weight (24% and 23%) and total grain yield (20% and 21%) in water-stressed mungbean plants of line 16003 and 16004, respectively, was recorded due to ALA seed priming than other modes of applications. Conclusions Conclusively, 0.1 and 0.15 mM levels of ALA as seed priming were found to reduce the adverse impact of water stress on mungbean yield that was associated with improved physio-biochemical mechanisms. Implications The findings of the study will be helpful for the agriculturalists working in arid and semi-arid regions to obtain a better yield of mungbean that will be helpful to fulfill the food demand in those areas to some extent.
Keywords: Antioxidation; Seed yield; Lipoic acid; Exogenous application; Deficit irrigation; Mungbean